Clearing the Air? Information Disclosure, Systems of Power, and the National Pollution Release Inventory - Simmons, Greg (McGill Law Journal / Revue de droit de McGill, 2013)
The establishment of the National Pollutant Release Inventory (NPRI) in 1992 marked the emergence of a new approach to the regulation of industrial pollution in Canada. In contradistinction to the traditional permit-based model of regulation, the NPRI sets no mandatory discharge limits, instead requiring facilities to track their releases of pollutants and report them to a publically-accessible national database. Through its grounding of regulation in the interplay of social actors interacting across the public/private divide, the NPRI exemplifies a new governance technique of environmental regulation, a characterization I examine through a series of analytical lenses. The mining industry offers an informative narrative, and I contend that the relationship between mining activity and the NPRI illustrates well the risks of failing to attend to the extant distribution of power within the social dynamic that informational regulatory mechanisms seek to harness. I end by offering some recommendations for how the NPRI might be improved in light of these considerations.